Emotional processes, leadership, gender and workplace affect in interdisciplinary teams - Tsouvelas, George; Nikolaou, Ioannis; Koulierakis, George (Psychology: the Journal of the Hellenic Psychological Society, 2022)
The purpose of this study was to analyze the role of emotional skills and gender in workplace affect through non-hierarchical level and multilevel analyses. Data was collected through self-report questionnaires completed by 19 directors and 128 subordinates working in interdisciplinary teams of Centers of Educational and Counselling Support. At non-hierarchical level, higher order emotional abilities (use and regulate emotions) were positively related to positive affect at workplace. Negative affect was negatively associated with the ability to regulate emotions and positively with the strategy of emotional suppression. At multilevel analyses, cognitive reappraisal emerged as a significant predictor for both the positive and negative affect (inversed) of the subordinates. Gender differences were observed at multilevel analyses. We tempt to explore possible tensions between emotional competencies and emotional outcomes (workplace affect) both at non-hierarchical level and managerial level in interdisciplinary teams. Training programs may promote group emotional empowerment and focus on higher order emotional skills. Managerial level training programs could also go deep in cognitive reappraisal of the emotions as an emotion regulation strategy that promotes safer emotional affect at workplace.